Comparative efficacy of psychological therapies for improving mental health and daily functioning in irritable bowel syndrome: A systematic review and meta-analysis. (February 2017) - Laird, Kelsey T.; Tanner-Smith, Emily E.; Russell, Alexandra C.; Hollon, Steven D.; Walker, Lynn S.
Abstract: Previous meta-analyses have shown that psychotherapy improves gastrointestinal symptoms in adults with irritable bowel syndrome (IBS); however, the impact on functioning in daily activities is unknown. Meta-analysis was used to estimate the effect of psychotherapy on mental health and daily functioning in adults with IBS. An extensive literature search located 28 eligible randomized controlled trials (RCTs) providing outcome data for mental health and 18 RCTs providing data for daily functioning. Compared to a mixed group of control conditions, psychotherapy produced significantly greater improvements to mental health ( d −  = 0.41) and daily functioning ( d −  = 0.43). Cognitive behavior therapy (CBT) was evaluated in the largest number of trials (21 trials), followed by hypnosis (4 trials), psychodynamic (3 trials), and relaxation (2 trials). The psychotherapeutic modalities were comparable with respect to their effect on mental health. CBT produced the greatest improvements to daily functioning, and this effect was significantly larger than that produced by relaxation therapy. These results have important clinical implications for treatment of adults with IBS. Highlights: A meta-analysis of 31 RCTs of psychotherapy for adults with IBS was conducted. Psychotherapy significantly improved both mental health and daily functioning. Several therapy modalities were similarly effective for improving mental health. Cognitive behavior therapy was most effective at improving daily functioning.